Sportonomics - Newsham, Gavin (Carlton, 2013)
"Is there a sport you could turn professional at with only a year of coaching? How much would it cost to run a Formula One car as your family runaround? How can you maximize your chances of playing international soccer against Lionel Messi? Why does being born in the summer prevent you from becoming a professional sports star? Which sport is the most profitable to participate in for the least amount of effort? These, plus many more, are the questions posed and answered by Sportonomics, a unique new book, which, through painstaking research, challenges us to use figures to take a quirky and sideways look at sport. Packed with well-investigated observations and explanations of hidden phenomenon, Sportonomics explores the many incredible idiosyncrasies that lay within world sport and will change your perceptions of the games we all love. Written in a fun and accessible style by a bestselling author and featuring astute observations that range from the technical and serious to fun and entertaining, Sportonomics will be a major sports talking point for the coming year."--Publisher's description.